Factors Affecting Pharmacists' Perceptions and Practices of Pharmacy Services during the Pandemic - Shahiroh Haulaini; Anna Wahyuni Widayati; Susi Ari Kristina (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Since WHO announced that COVID-19 is a global pandemic, there had been various changes in health services, including pharmaceutical services. Pharmaceutical preparations, medical devices, and consumable medical materials are pharmaceutical products in which the management is performed by pharmacists, so they must be managed wisely during this pandemic. This study aims to analyze what factors influence pharmacists' perceptions in doing pharmaceutical service during the COVID-19 pandemic. The study was conducted using a cross-sectional survey in which researchers distributed online questionnaires. Respondents were selected by convenience sampling with inclusion criteria: pharmacists who had practiced pharmacy services in Pharmacies and/or in public health centers (puskesmas) and/or in clinics and/or in hospitals in the Riau Islands province; had not participated in qualitative research and were willing to become research respondents. One hundred and fifteen respondents filled out questionnaires. We analyzed descriptively and statistically with Mann Whitney, Spearman Rank, and Kruskal Wallis test in Jamovi version 2.0. The level of significance for all statistical tests was set at p < 0,05. The results showed that of the 6 independent variables: age, gender, place of practice, length of practice experience, experience attending training/seminar related to COVID-19, and external factors, none of them influenced or correlated with the dependent variable: the role of pharmacists in management, the role of pharmacists in clinical pharmacy services as well as the development of the role and capacity of pharmacists during the pandemic. It can be concluded that there are no certain factors that affect the perception of pharmacists in doing pharmaceutical practices and services during pandemics based on statistical tests that have been done.